Consequences of coloniality on contemporary Iceland-Greenland relations - Helga Guðrún Númadóttir 1993- (2024)
Ritgerðin er lokuð til 15.04.2029 The Arctic's regional importance has grown substantially in recent years, owing to a rapidly changing climate and rising geopolitical tension. Parallel to these developments, Iceland's interest in strengthening bilateral ties with Greenland has grown steadily. Iceland and Greenland are close geographical neighbors in the North Atlantic with a number of shared interests and opportunities. However, until recently Greenland has not occupied a prominent role within Icelandic policymaking. As a matter of course, the recent elevation of priority has resulted in increased engagement and discussion about Greenland in Iceland. By adopting a postcolonial perspective, this thesis investigates how Iceland approaches its relationship with Greenland today, with an emphasis on how this can be understood with reference to past historical processes. In particular, the focus is on how Greenland has been constructed discursively in Iceland during certain periods and what this says about identity in Iceland. An important objective of the thesis is to advance the claim that contextualizing the role of the Greenlandic Other in the construction of Iceland’s national identity with current narratives about Greenland in Iceland can help to build a stronger partnership between the two countries. To this end, two different periods are studied: The Icelandic struggle for independence in the 19th and 20th centuries due to its importance for the emerging Icelandic identity, on the one hand, and contemporary discourses in Alþingi (the Icelandic Parliament) over a 10-year period (2010-2023), on the other. The analysis shows that whilst there has been a radical shift in narratives from historically not wanting to be associated with Greenland to an overwhelming inclination toward fostering stronger ties, European discourses of coloniality continue to influence how Iceland approaches its relationship with Greenland.